Moderasi Good Corporate Governance pada Pengaruh Kebijakan Dividen, Profitabilitas dan Ukuran Perusahaan terhadap Nilai Perusahaan - Jessica, Jessica; Arfianti, Rizka Indri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
Company value describes the condition of the company. Investors can find out whether the company is worthy of investment or not. The purpose of this study is to determine the effect of dividend policy, profitability and company size on company value with good corporate governance as a moderating variable in mining companies listed on the Indonesia Stock Exchange for the 2021-2023 period. The sampling technique used was purposive sampling and 24 companies were obtained, so that a sample of 72 samples was used. Hypothesis testing uses descriptive statistical analysis, regression coefficient similarity test to test data pooling, classical assumption test, multiple linear regression analysis and goodness of fit test. The conclusion of this study shows that there is sufficient evidence that profitability has a positive and significant effect on company value, while there is insufficient evidence that dividend policy and company size have an effect on company value. Next, good corporate governance is proven to be able to strengthen the influence of company size on company value, while good corporate governance is not proven to be able to strengthen the influence of dividend policy and profitability on company value.